A revision of the family Archinotodelphyidae Lang, 1949 (Copepoda: Cyclopoida: Oithonida), with the recognition of 15 new species - Kim, Il-Hoi; Boxshall, Geoff A. (Zootaxa, 2020)
The family Archinotodelphyidae Lang, 1949 is reviewed. Only the type genus, Archinotodelphys Lang, 1949, is accepted as valid and the genus Pararchinotodelphys Lang, 1949 is recognized as its junior subjective synonym. The two species formerly placed in the latter genus are transferred to the type genus as Archinotodelphys gurneyi (Illg, 1955) comb. nov. and A. phallusiae (Hansen, 1923) comb. nov. The species A. polynesiensis Monniot, 1986 was regarded as highly variable by Monniot (1986) but here we separate out his material from the host Herdmania momus (Savigny, 1816) which we recognise as a distinct species, A. momus sp. nov. Another 14 new species are described for the first time, from material collected at numerous localities across the global ocean. The new species are: A. curtus sp. nov. from Styela sp., A. illgi sp. nov. from an unknown host, A. hexasetosus sp. nov. from Molgula platybranchia Monniot C., 1970, A. cinctus sp. nov. from Bathystyeloides enderbyanus (Michaelsen, 1904), A. antarcticus sp. nov. from Molgula pedunculata (Herdman, 1881), A. monnioti sp. nov. from Pareugyrioides galatheae Millar, 1959 (type host) and P. digitus Monniot C., 1997, A. bimerus sp. nov. from an unidentified species of the family Molgulidae, A. longiseta sp. nov. from Styela sigma Hartmeyer, 1912, A. reductus sp. nov. from Pyura gangelion (Savigny, 1816), A. elegans sp. nov. from Polycarpa argentata (Sluiter, 1898), A. rostralis sp. nov. from Polycarpa nigricans Heller, 1878, A. longicaudatus sp. nov. from Microcosmus longicloa Monniot C. & Monniot F., 1991, A. nudus sp. nov. from a Polycarpa sp., and A. unisetosus sp. nov. from an unidentified phlebobranch ascidian host. A key to species is provided.